2022
DOI: 10.1038/s41598-022-18405-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health literacy on anxiety and depressive symptoms in pregnant women in Japan during the COVID-19 pandemic

Abstract: To investigate the relationships between communicative and critical health literacy (CCHL) and anxiety and depressive symptoms (ADs) in pregnant women during the coronavirus disease 2019 (COVID-19) pandemic. A cross-sectional study was conducted and 5466 pregnant women responded in Japan in September 2020. A Kessler 6 scale (K6) score ≥ 10, an Edinburgh Postnatal Depression Scale (EPDS) score ≥ 13, and four CCHL groups were analyzed using a logistic regression model and trend test. The proportions of pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Adequate health literacy is linked to lower disease activity and improved physical functioning among patients with rheumatic diseases [57]. A number of studies find that better health literacy is associated with lower risks for anxiety and depressive symptoms [52,[58][59][60]. Consistent with the findings, this current study shows that adults with adequate literacy are more likely to report no problems with anxiety/depression than those with inadequate literacy.…”
Section: Plos Onesupporting
confidence: 86%
“…Adequate health literacy is linked to lower disease activity and improved physical functioning among patients with rheumatic diseases [57]. A number of studies find that better health literacy is associated with lower risks for anxiety and depressive symptoms [52,[58][59][60]. Consistent with the findings, this current study shows that adults with adequate literacy are more likely to report no problems with anxiety/depression than those with inadequate literacy.…”
Section: Plos Onesupporting
confidence: 86%
“…Howevere, even such unenforceable lockdown, maternity checks among healthy pregnant women were reduced, attended delivery by families was restricted, and return to hometowns for delivery was refrained in many facilities following government requests. In addition, not only infected pregnant women, but also close contact pregnant women were restricted antenatal checkups until the end of the home care period [21][22][23] , and higher rates of anxiety and depression among pregnant women were reported during the epidemic 24,25 .Therefore, social changes have been observed since early in the pandemic and have both directly and indirectly impacted pregnancies. Morover, there is a study reporting delayed health-seeking due to canceled or postponed maternity care appointments, and avoiding or postponing hospital care visits due to fear of infection contributed to 44.7% of pregnancies with complications 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy can enhance people's understanding of COVID-19 symptoms, foster adherence to measures aimed at curbing the virus's spread (including hygiene practices, physical distancing, and behavioral changes), and support the uptake of COVID-19 vaccines [ 38 , 39 ]. Moreover, numerous studies have shown that individuals with adequate health literacy are less likely to suffer from mental health issues during the COVID-19 pandemic, such as depression, anxiety, and sleep disturbances [ 40 42 ]. However, research on the impact of health literacy on PTSD, particularly among patients with long COVID-19, remains limited.…”
Section: Introductionmentioning
confidence: 99%